2001
DOI: 10.1046/j.1365-8711.2001.04229.x
|View full text |Cite
|
Sign up to set email alerts
|

Radio-quiet quasar environments at 0.5 <= z <= 0.8

Abstract: We quantify the galaxy environments around a sample of 0.5≤z≤0.8 radio‐quiet quasars using the amplitude of the spatial galaxy–quasar correlation function, Bgq. The quasars exist in a wide variety of environments; some sources are located in clusters as rich as Abell class 1–2 clusters, whereas others exist in environments comparable to the field. We find that, on average, the quasars prefer poorer clusters of ≈Abell class 0, which suggests that quasars are biased tracers of mass compared with galaxies. The me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 119 publications
(268 reference statements)
5
39
0
Order By: Relevance
“…There is an abundance of circumstantial evidence in the literature connecting QSO activity at low redshifts with mergers and interactions (e.g., Heckman et al 1984;Hutchings et al 1988;Canalizo & Stockton 2001;Urrutia et al 2008). Not only do a number of low-redshift QSOs show signs of interactions and mergers, but there is also a tendency for QSO host galaxies to exist in only moderately rich environments (e.g., Dressler et al 1985;Ellingson et al 1991;Wold et al 2001;see, however, Martini et al 2007 for a counterexample), consistent with the results of quasar clustering studies, which suggests that quasars exist in halos of mass $10 12 -10 13 M ( Hopkins et al 2007a;da Angela et al 2008). In such environments, velocity dispersions are moderate, and interactions have their greatest effect.…”
Section: Introductionmentioning
confidence: 99%
“…There is an abundance of circumstantial evidence in the literature connecting QSO activity at low redshifts with mergers and interactions (e.g., Heckman et al 1984;Hutchings et al 1988;Canalizo & Stockton 2001;Urrutia et al 2008). Not only do a number of low-redshift QSOs show signs of interactions and mergers, but there is also a tendency for QSO host galaxies to exist in only moderately rich environments (e.g., Dressler et al 1985;Ellingson et al 1991;Wold et al 2001;see, however, Martini et al 2007 for a counterexample), consistent with the results of quasar clustering studies, which suggests that quasars exist in halos of mass $10 12 -10 13 M ( Hopkins et al 2007a;da Angela et al 2008). In such environments, velocity dispersions are moderate, and interactions have their greatest effect.…”
Section: Introductionmentioning
confidence: 99%
“…Radio galaxies, which are intimately connected with RLQs in unification models, also appear to reside in cluster environments at high redshift (Pentericci et al 2000). However, the dichotomy between radio-loud and radio-quiet properties is now being questioned by studies which have found that almost all QSO hosts are elliptical galaxies, regardless of radio-loudness (McLure et al 1999;Dunlop et al 2002), and that the environments of RLQs are statistically indistinguishable from those of RQQs, at least at z < ∼ 1 (Hutchings et al 1995;McLure & Dunlop 2001;Wold et al 2001;Finn et al 2001). At higher redshifts, there is evidence that galaxy density maybe higher around RLQs, although a milder overdensity is seen towards RQQs (see review by Hutchings 2001).…”
Section: Introductionmentioning
confidence: 99%
“…• Ditto for both radio-loud and radio-quiet AGNs, including presence in a full range of environments, from groups to rich clusters, at moderate redshift (McLure & Dunlop 2001;Wold et al 2001, though with a contrary vote in favor of dense environments from Finn et al 2001). …”
Section: Half Of All Three-sigma Results Are Wrongmentioning
confidence: 99%